Coinfection of Tuberculosis Pneumonia and COVID-19 in a Patient Vaccinated with Bacille Calmette-Guérin (BCG): Case Report - Luciani, Michelangelo (SN Compr Clin Med, 2020)
COVID-19 is a respiratory tract infection caused by the new coronavirus SARS-COV2 that can be complicated by acute distress respiratory syndrome and multiorgan failure. In light of the high rate of mortality associated with COVID-19, pharmacological and non-pharmacological strategies to prevent the infection are currently being tested. Among non-pharmacological preventive measures, vaccines represent one of the main resources for public health. It has been suggested that Bacille Calmette-Guérin (BCG) vaccine may protect individuals against infection from COVID-19 virus, and two clinical trials addressing this question are underway. Here, we report the case of a 32-year-old woman, vaccinated with BCG when she was 1 year old, who was diagnosed with apical tuberculous pneumonia of the right lung along with COVID 19 pneumonia.